Management and utilization of water hyacinth (Eichhornia crassipes ( Mart.) Solms) - Indulekha, V P (Department of Agronomy College of Horticulture, 2018)
Water hyacinth is one of the most productive plants on earth, but it is also considered as the world’s worst aquatic weed. The phytoremediation capacity of water hyacinth and its management through ecofriendly means like silage making, composting, and mulching were studied at the College of Horticulture, Vellanikkara. The phytoextraction capacity of water hyacinth was evaluated through a purposive sampling by collecting plant and water samples from 20 sites in central Kerala. These samples were analysed for various nutrients including heavy metals. To study the association of plant nutrients with water nutrients, cross tabulation was done and dependence of plant nutrient factor on water nutrient was measured through Chi-square. The Chi-square statistic was significant for N, P, Mg, and Ni indicating that the level of nutrients could be brought to a minimum through water hyacinth. The accumulation of heavy metals in water hyacinth was in the order Fe> Al> Mn> Zn> Cr> Ni> Co> Hg> Pb> As. Among them, Pb content in plant samples was within the permissible limit, but contents of Fe, Cu, Cr, Zn and Ni were beyond the safe limits. The quality and palatability of silage prepared with fresh and wilted water hyacinth with or without rice straw or guinea grass and using molasses, cassava flour, or rice bran as additives was investigated. Considering the quality parameters such as pH, odour, and palatability, wilted water hyacinth with molasses (5%) or cassava flour (10%) and wilted water hyacinth with cassava flour (10%) and rice straw (10%) or guinea grass (10%) are the best options for utilizing water hyacinth as silage. The composting experiment consisted of four methods viz., Bangalore method, Indore method, phospho-composting, and vermicomposting. All the prepared composts had neutral to slightly alkaline pH. The lowest C: N ratio was recorded with vermicompost (11.58) followed by Bangalore compost (12.68). Nitrogen content at 3 months after composting (MAC) was higher in vermicompost and Bangalore compost. The highest N content at 6 MAC was observed in vermicompost (1.75%). Phosphorus content was higher in phospho-compost at 3MAC and 6 MAC. There was no significant difference in K content of different composts at 3 MAC. Calcium, Mg and S contents were high in vermicompost. Micronutrients such as Zn, Cu, Co, and Ni were higher with Bangalore composting. Heavy metals such as As, Cd, and Pb were not detected in any of the composts. None of the composts contained heavy metals beyond safe limits. A field experiment involving three mulch materials–jack tree leaves, green water hyacinth, and coconut leaves–were compared with no mulching in turmeric for two years. All the mulch materials including water hyacinth had positive effects on most morphological and physiological parameters of turmeric such as plant height, number of leaves, leaf area index, leaf area ratio, and dry matter production. In both years, rhizome yield was also higher in plots mulched with organic debris compared to non-mulch control. Nutrient uptake by the crop was also higher with mulching compared to non-mulched plots. All the mulch materials substantially affected weed density and weed dry weight and reduced turmeric-weed competition for different growth factors.